Road To Customer Satisfaction: The Servqual Journey - Fransiska Oktalia Duha Gumano; Ray Octafian (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study was carried out at Resto Bebek Goreng Pak Eko with the objectives of examining and measuring the quality of service offered by restaurant personnel and determining the level of satisfaction experienced by customers who dined at the establishment. The research was conducted using a qualitative approach and a descriptive research method, which allows for a more in-depth presentation of the findings of the research. In this study, the methods for collecting data included interviews with restaurant staff, observations of interactions between employees and clients, and a review of the literature to gain a better understanding of the conceptual framework underlying Servqual. The outcomes of the research are a reflection of how guests feel about the quality of service they receive when dining at the restaurant. Based on the findings of the research, one can draw the conclusion that the service that customers receive from the staff of Resto Bebek Goreng Pak Eko may be classified as being of a high quality. The level of service that guests get meets and exceeds their expectations. This shows that the restaurant has been effective in maintaining high service standards and satisfying the expectations of their customers within the framework of the customers' happiness with the service that has been delivered.